2016
DOI: 10.1186/s12916-016-0710-7
|View full text |Cite
|
Sign up to set email alerts
|

Spatial transcriptome analysis reveals Notch pathway-associated prognostic markers in IDH1 wild-type glioblastoma involving the subventricular zone

Abstract: BackgroundThe spatial relationship of glioblastoma (GBM) to the subventricular zone (SVZ) is associated with inferior patient survival. However, the underlying molecular phenotype is largely unknown. We interrogated an SVZ-dependent transcriptome and potential location-specific prognostic markers.MethodsmRNA microarray data of a discovery set (n = 36 GBMs) were analyzed for SVZ-dependent gene expression and process networks using the MetaCore™ workflow. Differential gene expression was confirmed by qPCR in a v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 57 publications
2
33
1
Order By: Relevance
“…[101] As for PIR, it has been identified as a protective prognostic gene and been reported that high expression of PIR (p = 0.025, HR 0.62 (0.41-0.95); Q1 cut-off) predicts superior overall survival of GBM patients based on univariate analysis. [102] However, unlike the previous study, our results suggest that high expression of PIR (p = 0.018, HR 1.089(1.015-1.168)) predicts inferior overall survival of GBM patients. This discrepancy may lie in the reasons as follows: 1 The limitations of our study were as follows: (1) we performed our study based on integrated bioinformatics analysis, our results need further biological experiments validation.…”
Section: Survival Analysiscontrasting
confidence: 99%
“…[101] As for PIR, it has been identified as a protective prognostic gene and been reported that high expression of PIR (p = 0.025, HR 0.62 (0.41-0.95); Q1 cut-off) predicts superior overall survival of GBM patients based on univariate analysis. [102] However, unlike the previous study, our results suggest that high expression of PIR (p = 0.018, HR 1.089(1.015-1.168)) predicts inferior overall survival of GBM patients. This discrepancy may lie in the reasons as follows: 1 The limitations of our study were as follows: (1) we performed our study based on integrated bioinformatics analysis, our results need further biological experiments validation.…”
Section: Survival Analysiscontrasting
confidence: 99%
“…55 In IDH wild-type glioblastoma, DLL3 is mainly expressed in the tumor lesions contacting the subventricular zone (SVZ) but not involving the cortex, which is a prognostic marker of poor PFS. 56 However, in high-grade gliomas, DLL3 is defined as a proneural signature gene that is associated with longer survival, with DLL3/Notch signaling a major determinant of tumor growth. 57 In vitro experiments indicate that DLL3 expression is downregulated in glioma cells, the recovery of which can inhibit the survival, proliferation and invasiveness of glioma cells.…”
Section: Delta-like Ligands In Gliomasmentioning
confidence: 99%
“…This could explain why periventricular tumors are more likely to be multifocal and present relapses that are not contiguous with the primary site. Finally, tumors in the SVZ have a stem-like profile and are associated with specific genetic alterations that support cell growth, proliferation and survival via altered metabolic programs, centromere assembly, chromosome segregation, epigenetic modifiers and increased ribosomal biogenesis (Haskins et al, 2013;Jungk et al, 2016;Lin et al, 2017).…”
Section: Brain Cancers Arising From the Svz: Clinical Gliomas And Epementioning
confidence: 99%